Tune in, log on soaps, fandom, and online community - Baym, Nancy K. (New media cultures, 2000)
The work provides an introduction to on-line and audience issues through the study of an Internet soap opera fan group composed largely of women. The author shows that women can build good on-line communities, whilst welcoming male participation.
Keywords: Television soap operas : Social aspects : United States; Television soap operas : Electronic discussion groups